Acoustic and Vibration Control for an Underwater Structure under Mechanical Excitation - Shi-Jian Zhu (Shock and Vibration, 2014)
Acoustic and vibration control for an underwater structure under mechanical excitation has been investigated by using negative feedback control algorithm. The underwater structure is modeled with cylindrical shells, conical shells, and circular bulkheads, of which the motion equations are built with the variational approach, respectively. Acoustic property is analyzed by the Helmholtz integration formulation with boundary element method. Based on negative feedback control algorithm, a control loop with a coupling use of piezoelectric sensor and actuator is built, and accordingly some numerical examples are carried out on active control of structural vibration and acoustic response. Effects of geometrical and material parameters on acoustic and vibration properties are investigated and discussed.